Microbial Contamination and Antimicrobial Resistance in Use of Ophthalmic Solutions at the Department of Ophthalmology, Jimma University Specialized Hospital, Southwest Ethiopia. (15th April 2019) - Tamrat, Lemlem; Gelaw, Yeshigeta; Beyene, Getenet; Gize, Addisu
Abstract : Background . Eye drops are most frequently used medications in ophthalmology. The carriage of pathogenic organisms to eyes through the agency of eye drops has presented a serious problem for several decades. The objective of this study was to determine the magnitude of contamination and pattern of antimicrobial resistance of in-use ophthalmic solutions. Method . A cross-sectional study was conducted at the Department of Ophthalmology, Jimma University Specialized Hospital (JUSH), Southwest Ethiopia, from June to December 2015. Samples from all ophthalmic solutions from outpatient department, operation theaters, and wards after an average duration of use of two weeks were taken. Samples were cultured and organisms were identified; antimicrobial susceptibility testing was performed using standard microbial identification techniques. The data were analyzed using SPSS software. Chi-square test was done and associations were taken as significant ifP < 0.05 . Result . The rate of contamination of eye drops in the study setup was found to be 51/70 (72.8%). Frequency of contamination of eye drops found was to be statistically associated with the duration of use of eye drops. Contaminations of eye drops were high among patients who self-administer the medications and those individuals who apply the medication less frequently. Tips of the bottles were more often contaminated than the content of the eye drop. Majority of both Gram-positive and Gram-negative organisms were sensitive for most of the broad-spectrum antibiotics; however, there were a significant number of Gram-negative organisms resistant to almost all antibiotics used. Conclusion . There is high rate of contamination of eye drops in the setup (72.8%). Duration of use of eye drops is a significant factor associated with contamination. Knowing duration time of each container and patient education on eye drop administration technique are mandatory.